Alignment between executive compensation strategy and business strategy: a study of best practices - Zarenczansky, Claudia (2024)
Purpose: The main objective of this research is to identify the mechanisms adopted by the boards of directors and compensation committees of the companies listed in the B3 Novo Mercado segment to align the executive compensation strategy with the business strategy. Methodology: This is an applied and exploratory qualitative research, based on the method of interviews with specialists. Primary data was collected through interviews with board members and/or members of compensation committees with extensive experience in defining and approving executive compensation strategies. For content analysis, a three-level coding technique (open, axial, and theoretical) was applied using Atlas.TI software. Findings: The results obtained point to an evolution of the proposed theoretical model through the incorporation of subcategories of analysis that emerged from the empirical data collected in the interviews with specialists. Originality: The main contribution of this study is to point out the facilitating elements and main obstacles to the alignment between compensation strategy and business strategy, from the point of view of the experts involved in the process, and to propose a better practices guide for boards of directors and compensation committees.